Does transient serum phosphate or serum phosphate status cause chronic kidney disease-associated pruritus in peritoneal dialysis patients? A cross-sectional and group-based trajectory modeling study - Zijun Zhou; Hanqing Zhang; Yunze Xing; Tao Zhang; Yaxuan Fang; Yueqi Zhang; Hanqi Yang; Junchen Li; Yintao Zhang; Bo Yang (Renal Failure)
Background Chronic kidney disease-associated pruritus (CKD-aP) is a common complication in peritoneal dialysis (PD) patients. Whether serum phosphate is associated with CKD-aP is controversial. We identified the serum phosphate trajectories of PD patients in the last 3 months and investigated the effects of serum phosphate persistence on CKD-aP.Methods A total of 407 PD patients from the PD Center of the First Teaching Hospital of Tianjin University of Traditional Chinese Medicine were included. The 14-item UP-Dial was used to investigate the prevalence and clinical characteristics. PD patients were identified with different trajectories of serum phosphate by group-based trajectory modeling.Results The prevalence of CKD-aP in PD patients was 51.8%. Among 407 PD patients, four distinct serum phosphate trajectories were identified. Both transient serum phosphate and serum phosphate status were associated with CKD-aP. Transient serum phosphate was associated with an increased risk of CKD-aP [OR (95%CI): 2.28 (1.30–4.02), 2.24 (1.22–4.10), 3.04 (1.66–5.58), 2.12 (1.21–3.70), respectively]. Compared with the persistent low-level group, the gradual increase group was not associated with an increased risk of CKD-aP [OR (95%CI): 1.59 (0.77–3.26)]. Both the gradual decrease group and the persistent high-level group were positively associated with an increased risk of CKD-aP [OR (95%CI): 2.18 (1.30–3.66), 3.19 (1.60–6.36), respectively].Conclusion Our study confirmed the relationship between serum phosphate and CKD-aP within the past 3 months, to some extent explaining the controversy generated by previous studies. These results may help clinicians better understand the relationship between serum phosphate and CKD-aP and the importance of controlling serum phosphate.